Deficits in emotion recognition monitoring in dementia patients: Neuropsychiatry and behavioral neurology/Dementia. (7th December 2020) - Cordero, Indira Ruth Garcia; Migeot, Joaquín; Aquino, Alexia; Fittipaldi, Sol; Rivera, Mariano Díaz; Sedeño, Lucas; Garcia, Adolfo M.; Ibanez, Agustin
Abstract: Background: The capacity to ascertain other people's emotional states is crucial for establishing and maintaining social interactions. In particular, accurate recognition of facial expressions and beliefs about whether we trust what a face transmits are fundamental for guiding and adjusting this social behavior. Yet, although emotion recognition impairments are well documented in neurodegenerative diseases, the role of monitoring skills in this domain remains poorly understood in the field of dementia. Method: We recruited patients with behavioral variant frontotemporal dementia (bvFTD, n = 18), Alzheimer's disease (AD, n = 27), and demographically‐matched controls ( n = 38). Participants performed a classic test of facial expression recognition and, after each trial, they provided a confidence judgment about their performance. A monitoring index was calculated considering both performance on each emotion type and associated confidence ratings (with higher values of the index indicating worse monitoring). Then, whole‐brain grey matter volume was analyzed via voxel‐based morphometry (VBM) to track possible associations with the monitoring index. Results: Compared to controls, both groups of patients exhibited difficulties in monitoring negative emotions. Monitoring of disgust was specifically impaired in bvFTD, and monitoring of sadness and neutral faces, in AD. VBM results showed that, in bvFTD, reduced grey matter volume in areas belonging to the limbic system and subcortical regions was associated with emotion recognition deficits. Monitoring impairments were also related with different subcortical and cortical areas, including the prefrontal lobe, insula and the cingulate cortex. On the other hand, in AD, temporal and parietal areas were associated with emotion recognition and parietal and frontal regions, with monitoring. Conclusion: These results indicate that dementia patients present emotion recognition monitoring impairments and that these deficits are associated with damage of cortical and subcortical regions as well as limbic circuits. In both groups, recognition and monitoring of emotions shared several structural substrates. The monitoring impairments presented in bvFTD and AD could be related with the changes in social cognition and behavior that these patients presented in daily life. Therefore, these preliminary findings could contribute to a better understanding of emotion monitoring processes.